The sticky steps of the career ladder for engineers: the case of first-generation students in Germany. (1st January 2020) - Huesmann, Monika; Calveley, Moira; Smith, Paul; Forson, Cynthia; Rosenbaum, Lisa
Abstract : Although governments and higher education institutions across Europe are promoting agendas for widening the educational participation and increasing the social mobility of young people from lower socio-economic groups, very little has been written about the experiences of these individuals when seeking and entering employment. We aim to address this gap. Using a qualitative research approach, we explore the career expectations, experiences and limitations of first-generation university engineering students and graduates in Germany. The article draws upon the work of Pierre Bourdieu to demonstrate how social and cultural capitals instilled by parents and social peers are invaluable in developing personal and professional networks and eventual entry into the engineering professions. A lack of, or underdeveloped, capitals can inhibit career opportunities and ultimately the social mobility and professional choices of graduate engineers. Our research discovered that university graduates from less advantaged backgrounds face a 'class ceiling' at university, in obtaining an internship and then when gaining entry to and working in the engineering profession; they encounter 'sticky steps' at each stage of their career ladder.